2016
DOI: 10.1590/0102-33062015abb0199
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing seed germination in Cerrado grasses

Abstract: Few studies address the ecology of herbs of Cerrado grasslands, which are ecosystems where the long dry season, high temperatures, insolation, fire and invasive grasses greatly influencing germination and the establishment of plants. We assessed germination of 13 species of Poaceae from Cerrado grasslands under nursery conditions or in germination chambers, the latter with i) recently collected seeds and seeds after six months storage, ii) under constant and alternating temperatures, and iii) in the presence a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
28
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 26 publications
5
28
0
4
Order By: Relevance
“…In contrast to other studies in the Cerrado ecoregion that found positive outcomes using direct seeding of trees, forbs, and grasses (Silva et al ; Pellizzaro et al ), in our study, direct seeding of native grasses did not show itself to be an efficient way to restore either the dry or the wet cerrado grasslands. In climate chamber conditions, we recorded low germination rates, as has been observed for other nonwoody cerrado species (Le Stradic et al ; Kolb et al ; Pellizzaro et al ). Seed dormancy occurs in an expressive number of savanna species as a strategy to prevent germination under unfavorable environmental conditions for establishment (Ramos et al ; Escobar et al ), and low seed viability is reported by several savanna grass species (Carmona et al ; Le Stradic et al ; Kolb et al ).…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…In contrast to other studies in the Cerrado ecoregion that found positive outcomes using direct seeding of trees, forbs, and grasses (Silva et al ; Pellizzaro et al ), in our study, direct seeding of native grasses did not show itself to be an efficient way to restore either the dry or the wet cerrado grasslands. In climate chamber conditions, we recorded low germination rates, as has been observed for other nonwoody cerrado species (Le Stradic et al ; Kolb et al ; Pellizzaro et al ). Seed dormancy occurs in an expressive number of savanna species as a strategy to prevent germination under unfavorable environmental conditions for establishment (Ramos et al ; Escobar et al ), and low seed viability is reported by several savanna grass species (Carmona et al ; Le Stradic et al ; Kolb et al ).…”
Section: Discussionsupporting
confidence: 78%
“…In climate chamber conditions, we recorded low germination rates, as has been observed for other nonwoody cerrado species (Le Stradic et al ; Kolb et al ; Pellizzaro et al ). Seed dormancy occurs in an expressive number of savanna species as a strategy to prevent germination under unfavorable environmental conditions for establishment (Ramos et al ; Escobar et al ), and low seed viability is reported by several savanna grass species (Carmona et al ; Le Stradic et al ; Kolb et al ). In addition, some studies have pointed out the importance of microorganisms in the germination and establishment of savanna native grasses (Veenendaal et al ; Martins et al ), and these associations are still poorly understood in the cerrado vegetation.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…The higher soil moisture and the lower radiant energy can reduce soil temperature in the forested savanna. Furthermore, soil temperature would become more stable, hindering the germination of species that need fluctuations in temperature to break the dormancy of their seeds (Kolb et al 2016). These aspects can lead to a reduction in germination success of cerrado understorey plants and, thus, compromise the persistence of these species in the encroached community.…”
Section: Discussionmentioning
confidence: 99%
“…For restoration of tropical grasslands, knowledge is slowly increasing about the transfer (Le Stradic, Buisson & Fernandes, 2014a;Le Stradic et al, 2016;Pilon et al, 2018) and propagation of old-growth grassland species Oliveira et al, 2012;Le Stradic et al, 2014b;Gomes et al, 2018), yet for most ecosystems such information remains scarce or non-existent, particularly for herbaceous species (Fernandes, 2016). Complicating matters, emerging research on species of the Cerrado, Katanga copper outcrops (Central Africa), and Queensland (Australia), suggests that many graminoids -a functional group that is critical to ecosystem flammability and livestock forage -produce few seeds, much of which is of low quality (Silcock & Scattini, 2007;Boisson et al, 2015;Le Stradic et al, 2015;Kolb et al, 2016;Dayrell et al, 2017). As such, the opportunities for reintroduction and propagation via seed sowing, soil transfer, and hay transfer, are often extremely limited (Le Stradic et al, 2014a; but see Le Stradic et al, 2014b;Sampaio et al, 2015;Gomes et al, 2018;Pilon et al, 2018).…”
Section: (4) Reintroduction Of Grasses and Forbsmentioning
confidence: 99%